Pengaruh Shopping Lifestyle,Fashion Involvement, Hedonic Shopping Motivation Dan Price Discount Terhadap Impulse Buying (Studi Kasus Pada Konsumen Matahari Department Store Di Kecamatan Sukun) - Erdiana, Alifiah Nur; Arifin, Rois; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study examines the impact of Shopping Lifestyle,Fashion Involvement, Hedonic Shopping Motivation, and Price Discount on Impulse Buying among Matahari Department Store consumers in Sukun District. Using Malhotra's formula, a sample of 125 respondents was selected through purposive sampling, and data was gathered via questionnaires. Analysis was conducted with SPSS version 29, employing various tests such as validity, reliability, normality, classical assumptions, multiple linear regression, F-test, t-test, and R². The results show that all four factors significantly and positively influence Impulse Buying.  Keywords: Shopping Lifestyle,Fashion Involvement, Hedonic Shopping Motivation, Price Discount, Impulse Buying